Formed by the village and the church: The reception of Stanley Hauerwas’s theological ethics in Africa - Ngong, David Tonghou 1971- (2015)
While many African theologians have appropriated the thought of Stanley Hauerwas in their work, this article focuses on two theologians whose work demonstrates the influence of post-Enlightenment or postliberal ethics in general and Hauerwasian influence in particular. The article argues that elements of Hauerwasian Christian ethics, such as its insistence on virtue or character development in the context of a community (the church) and the embodied nature of Christian ethics made manifest through witness, provide a significant reminder to what African Christian ethics should be about. It also argues, however, that Hauerwasian ethics, if not critically engaged, has the potential to replicate some of the unsalutary moves that Western missionary Christianity made, and some contemporary forms of African Christianity still make, against African thought, such as the attempt to erase African cultural memory. In order to overcome this tendency to divorce African Christians from their cultural contexts, the complex nature of their moral formation, that is, their being morally formed by both the village and the church, needs to be taken seriously.
Keywords: Moral Formation; Stanley Hauerwas; Ethics; Church; Africa